2021
DOI: 10.5109/4480725
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Velocity Changes Across Tube Banks in One-directional and Bi-directional Flow Conditions

Abstract: The back-and-forth movement of flow in oscillatory flow condition that can be found in blood flow, thermoacoustic energy system and ocean wave can be categorized as bi-directional flow condition and heat transfer in this flow condition is not well understood. This paper reports an experimental investigation that compares temperature and velocity values between the onedirectional (the usual flow condition) and the bi-directional flow conditions. The experiment was done using thermoacoustic's standing wave rig w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…The purpose of the current investigation is to evaluate the effect of changing flow conditions on heat transfer performance across tube banks through experimental investigations. Earlier investigations confirmed that the bi-directional flow exhibits different velocity and temperature behaviors across the staggered tube banks heat exchanger compared to that of the one-directional flow condition [10,26,27]. The numerical results as shown in ref [27] provided insights into fluid dynamics aspect that supplement the experimental findings of [10].…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…The purpose of the current investigation is to evaluate the effect of changing flow conditions on heat transfer performance across tube banks through experimental investigations. Earlier investigations confirmed that the bi-directional flow exhibits different velocity and temperature behaviors across the staggered tube banks heat exchanger compared to that of the one-directional flow condition [10,26,27]. The numerical results as shown in ref [27] provided insights into fluid dynamics aspect that supplement the experimental findings of [10].…”
Section: Introductionmentioning
confidence: 58%
“…Since the flow in this promising thermoacoustic energy technology is bi-directional in nature, it is therefore important to understand the heat transfer nature between the heat exchanger and the flow when it is placed in thermoacoustic environment. The heat transfer performances of tube banks with staggered arrangement under one-directional and bi-directional flow conditions were reported earlier [10]. The change of orientation of the tube banks changes the fluid dynamics of flow around the tube banks and therefore the heat transfer behavior is expected to be different too.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Increasing motor efficiency is the most influential thing and must be considered in BLDC electric motors. Efficiency is always related to heat transfer and performance on BLDC motors 28) , so that the better the heat transfer efficiency, the better the cooling system [29][30][31] . One of the benchmarks of efficiency in a BLDC motor is heat transfer to the motor caused by the load received by the motor and the use of maximum speed, so it is one of the crucial factors in an electric motor design 32) .…”
Section: Introductionmentioning
confidence: 99%